Neo-Patrimonialism and Isomorphism in Moderating the Influence of Internal Control on Performance Accountability (Study at the office of National Civil Service Agency (BKN) in Indonesia) - Amru Sukmajati; Rohmat; Yosua Jaya Edy (STIE AAS Surakarta, 2021)
This research discusses the issue of the influence of internal control on performance accountability. Bureaucracy reform in Indonesia has entered the new round with regulation of the minister of administrative reform and Bureaucratic Reform No. 25 of 2020 on the Road Map of bureaucratic reform in 2020-2025. The research measures how far the readiness of the National Civil Service Agency (BKN) in realizing performance accountability through internal control. The researcha also takes the institutional theory approach of isomorphism and neo-patrimonialism theory as a development of previous research and is a novelty in this research. The sample processed was 99 respondents are APIP (Aparatur pengawas internal pemerintah) in BKN. Data processing using Structure equation Modeling (SEM) with Partial Least Square (PLS) approach. The results of the study are controlling positively on performance accountability. Mimetic and Normative Isomorphism moderate the influence of internal control on performance accountability. coersive isomorphism and Neo-patrimonialism do not moderate the influence of internal control on performance accountability.